2003
DOI: 10.3168/jds.s0022-0302(03)73583-8
|View full text |Cite
|
Sign up to set email alerts
|

Sialyloligosaccharides in Human and Bovine Milk and in Infant Formulas: Variations with the Progression of Lactation

Abstract: Several lines of research support a role for human milk oligosaccharides in the defense of breast-fed infants against pathogens. Some ofthese oligosaccharides contain at least one moiety of sialic acid and are, thus, termed sialyloligosaccharides. These constitute a significant component (>1 g/L) of human milk. It is well established that milk composition varies among species, and previous reports have indicated that one ofthe differences between human and bovine milk is precisely their contents of sialyloligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
173
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(212 citation statements)
references
References 31 publications
27
173
6
1
Order By: Relevance
“…The range of our CE results overlaps with the range of oligosaccharides reported by Kunz et al [8] for LST c, 6′-SL, and DSLNT (Table 7). Our range of results also overlaps with the results of the report of Martin-Sosa et al [28] for 6′-SL, 3′-SL, and DSLNT. There was a wide discrepancy between the values for LST a between these other two reports.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The range of our CE results overlaps with the range of oligosaccharides reported by Kunz et al [8] for LST c, 6′-SL, and DSLNT (Table 7). Our range of results also overlaps with the results of the report of Martin-Sosa et al [28] for 6′-SL, 3′-SL, and DSLNT. There was a wide discrepancy between the values for LST a between these other two reports.…”
Section: Discussionsupporting
confidence: 90%
“…Although this method allowed simultaneous analysis of both acidic and neutral species, many of the individual oligosaccharides could not be resolved. Martin-Sosa and associates described a method in 2003 of desialylating sialyloligosaccharides with neuraminidase, resolving them on an amino column, and detecting them at 206 nm [28]. Eight peaks were detected and quantified, but isomers of sialic acid attachment could not be resolved after desialylation, and the samples required extensive manipulation before analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, the total number of oligosaccharides in colostrum from individual cows ranged between 14 and 32 (Barile et al 2010). 3′ Sialylactose (3′SL), 6′ sialylactose (6′SL), 6′ sialylactosamine (6′SLN) and disialyllactose (DSL) are the predominant oligosaccharides in colostrum, with 3′SL accounting for 70% of the total oligosaccharide content (Martin-Sosa et al 2003;Nakamura et al 2003;McJarrow and van Amelsfort-Schoonbeek 2004;Tao et al 2009;Urashima et al 2009). Nakamura et al (2003 reported that levels of 3′SL, 6′SL and 6′SLN in colostrum were highest immediately following parturition and decreased rapidly by 48 h post-partum, whereas levels of neutral oligosaccharides increased.…”
Section: Oligosaccharidesmentioning
confidence: 99%
“…17 However, HMO specific composition is markedly affected by maternal genetic factors. 11,18,19 Different structures of oligosaccharides depend on the presence of specific transferase enzymes expressed in the lactocytes. The two genes involved in shaping the specific composition are the Secretor and the Lewis Blood Group genes.…”
Section: Carbohydratesmentioning
confidence: 99%